Editorial Preface - Ibrahim, Nabilah; Yunus, Riduan (International Journal of Integrated Engineering, 2019)
It is a great pleasure that we present the 11th special issue with a number of 7 of the International Journal of Integrated Engineering (IJIE). This edition features the latest findings and research in the areas related to Mechanical Engineering and its application. We would like to extend our sincere gratitude and appreciation for the enthusiastic and vigorous support and contributions from the Editorial Board and Reviewers of IJIE for taking time and effort to review the manuscripts.  As no manuscript is accepted or rejected without careful reading by experts in a particular area to which the paper is related. The experts have maintained a high standard of scholarship and we believe the readers of this Journal deserves. It is our hope that this fine collection of articles will be a valuable resource for International Journal of Integrated Engineering (IJIE) readers and will stimulate further research in the area of Mechanical, Materials and Manufacturing Engineering.  We strongly encourage authors to submit their articles and readers to provide feedback.  In order to access the online version of this issue along with archived editions please visit our website http://penerbit.uthm.edu.my/ojs/index.php/ijie/. We would like to thank all the authors who have contributed manuscripts in IJIE and those who are awaiting their manuscripts for publication in subsequent issues.